Inferring geographic origin, population structure and migration routes of a wintering population of Mediterranean gulls from resightings data. Issue 2 (24th February 2013) - Carboneras, Carles; Tavecchia, Giacomo; Genovart, Meritxell; Requena, Susana; Olivé, Marc; Oro, Daniel
Abstract: Winter congregations of migratory birds are made by individuals of different origins and generally assumed to be variable across space and time, but the demographic characteristics of these temporal populations are poorly known. We used 2, 216 observations of 472 colour‐ringed individuals to estimate the annual local survival of Mediterranean gulls Larus melanocephalus wintering in NE Spain. In addition, by gathering the ringing information on the 19, 856 individuals marked as fledglings in 18 countries between 1990 and 2009, we were able to infer the composition of population in relation to the country of origin. We coupled these estimates with geographic information to contrast hypotheses on the migratory pattern most likely used by the gulls in their first migration from their natal colonies to the wintering area. The probability of reaching the study area was negatively associated with the distance from the natal colony. Data were consistent with a migratory strategy that combines fluvial and coastal routes in an optimal way, seeking minimal distance along favourable terrain. We found that, after the first year, annual local survival at the wintering site (0.81 on average) was comparable with the one estimated at the breeding colonies, indicating a high individual fidelity to the areas used in winter. Our work shows that winter groupings may behave as real populations, shaped by breeding output and survival, and that the geographic origin of wintering birds can be explained by a simple model. The study of winter congregations can help understand a species' population structure and movement strategies.